Data from: Brown and polar bear Y chromosomes reveal extensive male-biased gene flow within brother lineages - Bidon, Tobias; Janke, Axel; Fain, Steven R.; Eiken, Hans Geir; Hagen, Snorre B.; Saarma, Urmas; Hallström, Björn M.; Lecomte, Nicolas; Hailer, Frank (Zenodo, 2015)
Brown and polar bears have become prominent examples in phylogeography, but previous phylogeographic studies relied largely on maternally inherited mitochondrial DNA (mtDNA) or were geographically restricted. The male-specific Y chromosome, a natural counterpart to mtDNA, has remained under-explored. Although this paternally inherited chromosome is indispensable for comprehensive analyses of phylogeographic patterns, technical difficulties and low variability have hampered its application in most mammals. We developed 13 novel Y-chromosomal sequence and microsatellite markers from the polar bear genome, and screened these in a broad geographic sample of 130 brown and polar bears. We also analyzed a 390 kb-long Y-chromosomal scaffold using sequencing data from published male ursine genomes. Y chromosome evidence support the emerging understanding that brown and polar bears started to diverge no later than the Middle Pleistocene. Contrary to mtDNA patterns, we found (i) brown and polar bears to be reciprocally monophyletic sister (or rather brother) lineages, without signals of introgression, (ii) male-biased gene flow across continents and on phylogeographic time scales, and (iii) male dispersal that links the Alaskan ABC-islands population to mainland brown bears. Due to female philopatry, mtDNA provides a highly structured estimate of population differentiation, while male-biased gene flow is a homogenizing force for nuclear genetic variation. Our findings highlight the importance of analyzing both maternally and paternally inherited loci for a comprehensive view of phylogeographic history, and that mtDNA-based phylogeographic studies of many mammals should be re-evaluated. Recent advances in sequencing technology render the analysis of Y chromosomal variation feasible, even in non-model organisms. Y STR Allele sizes A table of allele sizes of 9 Y STR markers from 134 individuals Submission DRYAD allele sizes.xlsx